Some modifications of conjugate gradient coefficient for unconstrained optimization - Mohd Rivaie Mohd Ali (Fakulti Sains dan Teknologi, 2011)
Conjugate gradient methods hold an important role in unconstrained optimization. Numerous studies and modifications have been done recently to improve this method. However, these new modifications tend to be complicated and difficult. In this research, three new simple modifications of conjugate gradient coefficient (J3k) for solving unconstrained optimization problems have been proposed.